Pengaruh Konsentrasi Sodium Alginat Terhadap Boba Kulit Buah Naga (Hylocereus Polyhizus) Menggunakan Teknik Spherifikasi Dasar - Ningrum, Cicik Agustia; Yuniati, Yuyun; Sucahyo, Bambang Sigit (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Usually, dragon fruit is only used for the flesh while the skin is discarded and considered waste. Dragon fruit peel contains vitamin C, vitamin E, vitamin A, alkaloids, terpenoids, flavonoids, thiamine niacin, pyridoxine, cobalamin, phenolics, carotene and phytoalbumin. 30-35% of dragon fruit is the skin of the fruit but it is often just thrown away as trash. Dragon fruit skin contains quite a lot of the natural dye anthocyanin. This research aims to determine the effect of pH, water content, vitamin C, and organoleptics on the of dragon fruit skin boba using the basic spherificatiom technique. This research used laboratory experimental methods using a completely randomized design (CRD) with varying concentrations of sodium alginate (1gr,1,1gr,1,2gr,1,3gr, dan 1,4gr) calcium lactate (5 grams) for each treatment. This was repeated 3 times, the analyzes tested in this study were pH, viscosity and organoleptic tests. The parametric data obtained were analyzed using analysis of variance (ANOVA) using statistical product and service solution (SPSS) version 23 data and for non-parametric data using Kruskal Wallis.